Thin Aerofoil with Multiple Slotted Flap - T.S. Patel; T.A. Derbasi; A.N. Hassanen (Engineering Transactions, 1988)
The paper deals with the problem of thin aerofoil with multiple slotted movable hinge flaps. Two particular cases are considered: a) assuming no gaps exist at the hinges, and b) considering the existence of slots. The conventional assumptions of small angle of attack, small flap deflection and small camber are omitted.